The onward migration-family nexus: the lived experiences of London's onward Colombian migrants from Spain and their families - Turcatti, D (2023)
This research investigates the onward migration-family nexus by centring the lived experiences of Colombian families who onward migrated from Spain to London after the 2008 global financial crisis. Onward migration can be broadly defined as the process whereby migrants leave the country in which they settled for a period of time and migrate to another country when circumstances change. In this thesis, the onward migration-family nexus is understood as the complex ways in which families shape onward migration and the multifaceted transformations they undergo as a result.